Integration Questions

Question Number 41351 by vajpaithegrate@gmail.com last updated on 06/Aug/18

$$\int_{\mathrm{0}} ^{\infty} \left[\frac{\mathrm{5}}{\mathrm{e}^{\mathrm{x}} }\right]\mathrm{dx}= \\$$

Commented by math khazana by abdo last updated on 06/Aug/18

$${let}\:{I}\:=\:\int_{\mathrm{0}} ^{\infty} \:\:\left[\frac{\mathrm{5}}{{e}^{{x}} }\right]{dx}\:{changement}\:\:\frac{\mathrm{5}}{{e}^{{x}} }\:={t}\:{give} \\$$$${e}^{{x}} =\frac{\mathrm{5}}{{t}}\:\Rightarrow\:{x}={ln}\left(\frac{\mathrm{5}}{{t}}\right)\:={ln}\left(\mathrm{5}\right)−{ln}\left({t}\right)\:\Rightarrow{dx}=−\frac{\mathrm{1}}{{t}}{dt} \\$$$${I}\:=−\:\int_{\mathrm{5}} ^{\mathrm{0}} \:\:\left[{t}\right]\frac{−{dt}}{{t}}\:=\:−\int_{\mathrm{0}} ^{\mathrm{5}} \:\:\frac{\left[{t}\right]}{{t}}\:{dt} \\$$$$=−\sum_{{k}=\mathrm{0}} ^{\mathrm{4}} \:\:\int_{{k}} ^{{k}+\mathrm{1}} \:\:\frac{{k}}{{t}}\:{dt}\:=−\sum_{{k}=\mathrm{1}} ^{\mathrm{4}} \:\int_{{k}} ^{{k}+\mathrm{1}} \:\frac{{k}}{{t}}{dt} \\$$$$=−\sum_{{k}=\mathrm{1}} ^{\mathrm{4}} {k}\:\left\{{ln}\left({k}+\mathrm{1}\right)−{ln}\left({k}\right)\right\} \\$$$$=\sum_{{k}=\mathrm{1}} ^{\mathrm{4}} {k}\left\{{ln}\left({k}\right)−{ln}\left({k}+\mathrm{1}\right)\right\} \\$$$$=−{ln}\left(\mathrm{2}\right)+\mathrm{2}\left\{{ln}\left(\mathrm{2}\right)−{ln}\left(\mathrm{3}\right)\right\}\:+\mathrm{3}\left\{{ln}\left(\mathrm{3}\right)−\mathrm{2}{ln}\left(\mathrm{2}\right)\right\} \\$$$$+\mathrm{4}\left\{\mathrm{2}{ln}\left(\mathrm{2}\right)−{ln}\left(\mathrm{5}\right)\right. \\$$$$\left.=−{ln}\mathrm{2}\right)+\mathrm{2}{ln}\left(\mathrm{2}\right)−\mathrm{2}{ln}\left(\mathrm{3}\right)+\mathrm{3}{ln}\left(\mathrm{3}\right)−\mathrm{6}{ln}\left(\mathrm{2}\right) \\$$$$+\mathrm{8}{ln}\left(\mathrm{2}\right)−\mathrm{4}{ln}\left(\mathrm{5}\right) \\$$$${I}\:=\mathrm{3}{ln}\left(\mathrm{2}\right)\:+\mathrm{3}{ln}\left(\mathrm{3}\right)−\mathrm{4}{ln}\left(\mathrm{5}\right)\:. \\$$$$\\$$

Commented by vajpaithegrate@gmail.com last updated on 06/Aug/18

$$\mathrm{thank}\:\mathrm{u}\:\mathrm{sir} \\$$

Commented by math khazana by abdo last updated on 06/Aug/18

$${nevermind}\:{sir} \\$$

Answered by MJS last updated on 06/Aug/18

$${f}\left({x}\right)=\left[\frac{\mathrm{5}}{\mathrm{e}^{{x}} }\right] \\$$$$\mathrm{ln}\:\frac{\mathrm{5}}{\mathrm{6}}<{x}\leqslant\mathrm{ln}\:\frac{\mathrm{5}}{\mathrm{5}}\:=\mathrm{0}\:\Rightarrow\:{f}\left({x}\right)=\mathrm{5} \\$$$$\mathrm{0}<{x}\leqslant\mathrm{ln}\:\frac{\mathrm{5}}{\mathrm{4}}\:\Rightarrow\:{f}\left({x}\right)=\mathrm{4} \\$$$$\mathrm{ln}\:\frac{\mathrm{5}}{\mathrm{4}}<{x}\leqslant\mathrm{ln}\:\frac{\mathrm{5}}{\mathrm{3}}\:\Rightarrow\:{f}\left({x}\right)=\mathrm{3} \\$$$$\mathrm{ln}\:\frac{\mathrm{5}}{\mathrm{3}}<{x}\leqslant\mathrm{ln}\:\frac{\mathrm{5}}{\mathrm{2}}\:\Rightarrow\:{f}\left({x}\right)=\mathrm{2} \\$$$$\mathrm{ln}\:\frac{\mathrm{5}}{\mathrm{2}}<{x}\leqslant\mathrm{ln}\:\mathrm{5}\:\Rightarrow\:{f}\left({x}\right)=\mathrm{1} \\$$$${x}>\mathrm{ln}\:\mathrm{5}\:\Rightarrow\:{f}\left({x}\right)=\mathrm{0} \\$$$$\Rightarrow \\$$$$\underset{\mathrm{0}} {\overset{\infty} {\int}}\left[\frac{\mathrm{5}}{\mathrm{e}^{{x}} }\right]{dx}=\mathrm{4ln}\:\frac{\mathrm{5}}{\mathrm{4}}\:+\mathrm{3}\left(\mathrm{ln}\:\frac{\mathrm{5}}{\mathrm{3}}\:−\mathrm{ln}\:\frac{\mathrm{5}}{\mathrm{4}}\right)+\mathrm{2}\left(\mathrm{ln}\:\frac{\mathrm{5}}{\mathrm{2}}\:−\mathrm{ln}\:\frac{\mathrm{5}}{\mathrm{3}}\right)+\mathrm{ln}\:\mathrm{5}\:−\mathrm{ln}\:\frac{\mathrm{5}}{\mathrm{2}}= \\$$$$=\mathrm{ln}\:\frac{\mathrm{625}}{\mathrm{24}}\:\approx\mathrm{3}.\mathrm{25970} \\$$

Commented by vajpaithegrate@gmail.com last updated on 06/Aug/18

$$\mathrm{thank}\:\mathrm{u}\:\mathrm{sir} \\$$